Analisis Penerapan Laporan Keuangan Menurut Isak 35 Dan Penerapan Rencana Kegiatan Dan Anggaran Sekolah (Arkas) - Anggi Sutisna; Elan Eriswanto (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The application of ISAK 35 is by allowing non-profit entities to adapt the descriptions used for some items contained in the financial statements as well as the financial statements themselves. The RKAS application (School Activity Plan and Budget) is an information system created to deal with school financial management issues starting from the process of planning, organizing, directing, coordinating, supervising or controlling. SMP Negeri 1 Cibitung has not implemented or made financial reports in accordance with ISAK 35, however SMP Negeri 1 Cibitung has implemented ARKAS in making financial reports on BOS funds but there are still problems in its application. The purpose of this research is to analyze the application of ISAK 35 and find out the application of the School Activity Plan and Budget (ARKAS) Application at Cibitung 1 Public Middle School. The type of data used is primary and secondary data. Data collection techniques were carried out by observation, interviews and documentation. The data analysis method used is descriptive qualitative. The results of this study are that the form of financial reports at SMP Negeri 1 Cibitung in 2022 has been adjusted according to ISAK 35 and SMP Negeri 1 Cibitung has applied or used ARKAS in making financial reports on BOS funds.